PENGARUH KUALITAS PRODUK, PROMOSI DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN MENGGUNAKAN APLIKASI SHOPEEFOOD (Studi Pada Konsumen Nasi Goreng Dan Bakmie Bang Najib) - Scorina Dwiantari; Rusdiana Permanasari (JURNAL ILMIAH EDUNOMIKA, 2023)
In the current era we have entered where everything has been based on technology. The technology in question is the internet. Indonesian people use internet services for daily activities such as online shopping because it is considered practical and safe, one of the food delivery service providers is Shopeefood. One of the businesses that uses the Shopeefood application is Special Fried Rice and BakmieBang Najib. It is expected that sales through shopeefood will increase compared to direct sales, but the fact that sales through the Shopeefood application is smaller compared to direct sales. The purpose and target of this study is to find out how much influence product quality factors, promotions and service quality have on purchasing decisions using the Shopeefood application. The sampling technique uses Purposive Sampling Technique. Data analysis using SEM – PLS 4 analysis. The results achieved are product quality has a positive and significant effect on purchasing decisions, it is proven that the path coefficient is equal to the path coefficient of 0.453 (t = 5.447; p